2011
DOI: 10.1038/cgt.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

Competitive electroporation formulation for cell therapy

Abstract: Established cell transfection via nucleofection relies on nucleofection buffers with unknown and proprietary makeup due to trade secrecy, inhibiting the possibility of using this otherwise effective method for developing cell therapy. We devised a three-step method for discovering an optimal formulation for the nucleofection of any cell-line. These steps include the selection of the best nucleofection program and known buffer type, selection of the best polymer for boosting the transfection efficiency of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Since Flanagan and colleagues have shown that certain polymers can boost the transfection efficiency for some cells [34], we asked whether different amounts of polyethylene glycol (PEG - 0.01, 0.1 and 1%) added to 2S buffer during electroporation could augment the number of viable cells and transgene expression in mouse T cells. We observer no positive impact on cell viability whereas slight variations in GFP expression were observed; however, solution 2S achieved higher percentages of GFP positive cells in the absence of PEG (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Since Flanagan and colleagues have shown that certain polymers can boost the transfection efficiency for some cells [34], we asked whether different amounts of polyethylene glycol (PEG - 0.01, 0.1 and 1%) added to 2S buffer during electroporation could augment the number of viable cells and transgene expression in mouse T cells. We observer no positive impact on cell viability whereas slight variations in GFP expression were observed; however, solution 2S achieved higher percentages of GFP positive cells in the absence of PEG (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Following our optimized nucleofection method developed previously [10], we initially chose two buffers: OptiMEM and pulsing buffer. To determine the nucleofection program that would yield the highest effectiveness, we used the following seven programs, as outlined in the Amaxa Nucleofector Optimization Protocol: A-20, T-20, T-30, X-01, X-05, L-29, and D-23.…”
Section: Resultsmentioning
confidence: 99%
“…ADSC were nucleofected with a plasmid coding for a protein involved in angiogenesis and cell proliferation: Sonic Hedgehog (Shh). In this study, the choice of nucleofection method of Shh gene was based on two arguments: (1) this technique allows the genetic material to be delivered directly into the nucleus [114,115], resulting in higher transfection efficiency than electroporation [116], (2) this technique does not alter the phenotype and potential multilineage of ADSC [117]. In this in vivo study, we checked that nucleofection technique allowed the production of sufficient amounts of transfected ADSC to be grafted to a large animal model [113].…”
Section: Stem Cell Therapy Strategies Under Assessmentmentioning
confidence: 99%